2013
DOI: 10.4238/2013.december.16.7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and fast preparation of biologically active recombinant human coagulation factor VII in CHO-K1 cells

et al.

Abstract: ABSTRACT. Human coagulation factor VII (FVII) plays an important role in the blood coagulation process and exists in micro amounts in human plasma; therefore, any attempt at the large-scale production of FVII in significant quantities is challenging. The purpose of this study was to express and obtain biologically active recombinant FVII (rFVII) from Chinese hamster ovary K1 (CHO-K1) cells. The full-length FVII cDNA was isolated from a HepG2 cell line and then subcloned in pcDNA3.1 to construct an expression v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…23 Low expression of rFVII in these studies may be caused by the low cell density and short culture time of adhered cells. Therefore, suspension culture already the main method used to produce therapeutic proteins should be developed and applied to rFVII expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Low expression of rFVII in these studies may be caused by the low cell density and short culture time of adhered cells. Therefore, suspension culture already the main method used to produce therapeutic proteins should be developed and applied to rFVII expression.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal combination of culture and feed media resulted in 20 mg/L of rFVII expression in CHO cells, a result that is higher than previously reported studies. 2,4,5,23 Moreover, it has been reported that the cell cycles phase, specifically the percentage of cells in the G0/G1 phase, significantly influences the specific productivity and production of recombinant proteins in CHO cells. [16][17][18][19] Many researchers have focused on screening for chemicals that pause the cells in the G0/ G1 phase to enhance protein specific productivity in CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…FVII is consisted of 406 residues of a single peptide chain, with a molecular weight of 50 KD, and the plasma levels of FVII are influenced by both genetic and environmental factors . FVII is one of the key molecules involved in blood clot formation, which plays an important role in blood coagulation process and induces the generation of fibrin during the coagulation process . Common polymorphisms (−323 0/10 bp, −401 G/T, −402 G/A) at the FVII gene locus may modulate FVII gene transcription, thus exerting an effect on plasma FVII protein levels .…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, os trabalhos publicados até o momento também possuem em comum o fato de utilizarem vetores não virais e a utilização de drogas como pressão seletiva para geração de uma linhagem celular mais estável (WAHJI et al, 2008;XIAO et al, 2013). Em relação à produção, a maioria dos trabalhos mostrou uma expressão em torno de 270 a 500 ng/mL de FVIIr, com exceção do trabalho de Kemball-Cook (1994), que relata a produção de 5000 ng/mL (KEMBALL-COOK et al,…”
Section: Discussionunclassified